Modelo de processo de software na Universidade Federal do Espírito Santo : uma formulação baseada no arcabouço legal - Capistrano, Alvaro Guilherme Ayres (2016)
This work aims to develop a software process model at the Universidade Federal do Espírito Santo (UFES) based on the current legal framework. Through this work it was possible to perceive that the Federal Public Administration issued a series ofstandards for the Information Technology and Communications (ICT) sector that were not being fulfilled by the public entity in question. In this way, it was investigated which norms legislated on the development of systems, mapped their respective processes, activities and artifacts and created a methodology that could serve them. The work made use of bibliographic research and applied research as research types and took as basis the principles of software engineering and software process, being validated by the direction of the Núcleo de Tecnologia da Informação. As a result we have the model that meets the legal framework and can be implemented gradually.